The Contribution of Islamic Religious Education in Building Students' Character - Wahid Hakim Azzaky; Mahfud Junaedi; Abdul Wahib (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
Islamic Religious Education (PAI) plays a crucial role in shaping the moral character of students, especially in the era of globalization, which is filled with social and moral challenges. PAI not only serves as a means of transferring religious knowledge but also as a medium for internalizing fundamental moral values such as honesty, responsibility, and empathy. This research identifies various challenges faced in the implementation of moral education, including the negative influence of social media and the lack of parental involvement. Using the library research method, this study analyzes relevant literature to evaluate the effectiveness of PAI in building character. The results show the need for curriculum reform that is more relevant and teaching approaches that are more applicable. The synergy between schools, families, and communities is essential to ensure that moral values are internalized in students' daily lives. With teachers as role models, it is hoped that PAI can produce a generation that is not only academically intelligent but also of noble character and ethics.